Essentiality of work - Helfen, Markus; Delbridge, Rick; Pekarek, Andreas; Purser, Gretchen (Emerald Publishing Limited, 2024)
The Covid-19 pandemic both popularized and politicized the designation of essential work. Interrogating the dialectics of essential work, this volume of Research in the Sociology of Work presents original research that explores the essentiality of work and highlights the experiences of essential workers during the pandemic, drawing on empirical studies in Canada, Germany, the United Kingdom and the United States. Demonstrating an enduring struggle for recognition and dignity, as well as for revaluing and materially rewarding essential work, contributors examine the emotional labour involved in gendered care work, the impact of COVID-19 on residential care work, the politics of essentiality and the diversity and intersectional inequality of essential workforces. The final chapters are the first of a new recurring section spotlighting ethnography by presenting both new empirical research and in-depth reviews of extant contributions. Raising pressing questions about the essence of work and its place in contemporary society, Essentiality of Work inspires new debates about the centrality of the work experience and how labour is understood in modern life both for those undertaking work as well as those who benefit.
Includes index.
Keywords: Work.; COVID-19 Pandemic, 2020- -- Influence.; Social Science -- Sociology -- General.; Sociology: work and labour.; Sociology.; elektronické knihy; electronic books